AGRICULTURAL SUSTAINABILITY AND SOCIAL RESPONSIBILITY - Đukić, Marijana; Uzelac, Ozren; Stoiljković, Aleksandra (Economics of Agriculture, 2021)
Exchange of the drought and precipitations due to climate changes is preventing higher agrarian output. Although modern technology and methods of farm production may be the answer to this question, these raise public concerns about employment and environment quality. Because of demographic and technological lagging, some countries face other problems of achieving agronomic sustainability. In this paper, the importance of sustainable agriculture development, legal bases and some aspects of agricultural social responsibility are explored. Comparative and logical deduction methods of reviewing the selected international and national documents and literature were employed. Authors conclude there are adequate legal frameworks for agricultural social responsibility and the discussion if agriculture’s moral priorities affect its economic performance will never end.